Protective Effect of [Cu(Nn1)2](Clo4) Complex in Rainbow Trout Challenged Against Flavobacterium Psychrophilum - Guerrero-Nunez, J; Guerrero-Nunez, J; Modak-Canobra, B; Segura-Segura, R; Segura-Segura, R; Tello-Reyes, M; Soto-Aguilera, S; Arce-Ortega, P; Arce-Ortega, P; Aldabaldetrecu-Urbieta, M; Aldabaldetrecu-Urbieta, M; Paz de la Vega-Quiroz, A; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Previously, we reported an in vitro evaluation regarding antibacterial effects against F. psychrophilum by a new Cu (I) complex, [Cu(NN1)2](ClO4). This study presents the results of an in vivo evaluation of [Cu(NN1)2](ClO4) added as a dietary supplement against F. psychrophilum in rainbow trout. The results showed that the administration of [Cu(NN1)2](ClO4) at 29 and 58 µg/g of fish for 15 days does not affect the growth of rainbow trout. On the other hand, the amount of copper present in the liver, intestine, and muscle of rainbow trout was determined. The results showed that the amount of copper in the liver, when compared between treated fish and control fish, does not change. While, in the intestine, an increase in the fish fed at 58 µg/g of fish was observed. In muscle, a slight decrease at 29 µg/g was obtained. Additionally, copper concentrations in the pond water after 15 days of feeding with the [Cu(NN1)2](ClO4) complex showed the highest levels of copper. Finally, the effect of the administration of [Cu(NN1)2](ClO4) for 15 days at 58 µg/g of fish was evaluated against F. psychrophilum, where a 75% survival was obtained during 20 days of challenge. © 2022 by the authors.
Keywords: Flavobacterium psychrophilum; copper (I) complex; antibacterial activity; coumarin; rainbow trout